Food insecurity and disability among working-age and older adults - Mia Hadfield-Spoor; Mauricio Avendano; Rachel Loopstra (Cambridge University Press, 2024)
Abstract Objective: To explore relationships between disability, food insecurity (FI) and age and examine how socio-economic factors impact risk of FI among disabled people in working and older age. Design: Logistic regression models used to analyse the contribution of socio-economic factors to gaps in risk of FI for disabled people. In models stratified into working and older age groups, differences in risk of FI for disabled and non-disabled people were examined by employment, education and assets. Setting: England, Wales and Northern Ireland, 2016 and 2018 Participants: A representative sample of 6187 adults aged 16+, of whom 28 % were disabled, from the Food & You survey. Results: The gap in FI risk by disability status decreased as age increased. For ages 25-34 for disabled v. non-disabled people, risk of FI was 31 % (95 % CI 21-41 %) v. 10 % (8-12 %); at ages 45 to 54, it was 18 % (11-23 %) v. 7 % (5-8 %), and at ages 75+, there was no gap in risk. Accounting for socio-economic variables halved the gap in risk among working ages. However, among working-age adults, FI among disabled people in full-time work was 15 % (11-20 %) compared with only 7 % (6-9 %) among non-disabled people in full-time work. Among older people, disabled people without savings were at higher risk of FI (5 % (3-7 %)) than non-disabled people without savings (2 % (1-3 %)) but having savings closed risk gap. Conclusions: Socio-economic resources partially explain disparities in FI risk when disabled. Disparities remained for people in full-time work and among people without savings in older age.